30 Genotypic effects of a Dopamine receptor type-2 SNP on growth and semen quality in beef bulls exposed to a dopamine agonist. (29th July 2019) - DeCarlo, Andrea N; Jennings, Kaysie; Pratt, Scott; Burnett, Callie; Long, Nathan; Bridges, William; Kojima, Cheryl
Abstract: Ergot alkaloids (EA) share similar structural properties to neurotransmitters and are able to elicit physiological responses in cattle that consume them by binding receptors such as the Dopamine type-2 receptor (DRD2). A single nucleotide polymorphism (SNP) in DRD2, previously found to be correlated to prolactin (PRL) serum concentrations was evaluated for impact on growth traits and semen quality parameters. Yearling beef bulls were allowed to graze a diet containing (E+) (n = 41) or lacking EA (E-) (n = 43) over a four-year study. Blood samples and semen were collected every 21 or 28 d. Semen motility, morphology, body condition score (BCS) and scrotal circumference (SC) were recorded. Prolactin (PRL) serum concentrations were assessed by radioimmunoassay (RIA). Bulls were sacrificed from the first year at the end of a 126-day period or 60 days after removal of treatment. Testicles and epididymis were collected and immunohistochemistry was performed on testis, epididymis, and sperm cells. Tissues and cells were incubated in the presence or absence of primary antibody against DRD2 with a DAPI counterstain. Isolation of DNA was performed on sperm pellets from semen collected using DNAzol (Thermo Fisher Scientific, Waltham, MA, USA). Amplification of the DRD2 SNP region was performed by PCR and resulting products were assessed for genotype through restriction fragment length polymorphism (RFLP) analysis. These data show the presence of DRD2 in the testis, epididymis, and sperm cells; however, semen quality and growth traits did not differ across DRD2 genotype or treatment. Body condition (P = 0.0009), SC (P = 0.0053), and semen velocity (P = 0.0398) differed across period. As expected, consumption of EA resulted in decreased prolactin serum concentrations (P = 0.0240)